Ethnocultural Factor of Inclusive Education Development (by the Examples of the Russian Federation and Kyrgyz Republic) - M. A. Suchkov (Высшее образование в России)
The article addresses the problems of inclusive education development through the prism of ethnocultural factors. A small comparative analysis of inclusive education development is given: legislative and law basis, cultural traditions in Russia and Kyrgyzstan, language and customs. The ethnocultural factor of inclusive education development is expressed through the language of “study” at schools and professional educational organizations. The author emphasizes the signs of our time – language assimilation in the countries of the former Soviet Union. It is shown that many parents in the north of Kyrgyzstan send their children, including children with disabilities, to study at Russian schools, and it causes additional barriers in learning, along with the barriers caused by physical and intellectual disabilities.